The determinants of excess liquidity in the banking sector of Bosnia and Herzegovina - Elma Hasanović; Tanja Latić (Graduate Institute of International and Development Studies, 2017)
The aim of this research is to identify the determinants of excess liquidity defined as excess reserves in the banking sector in Bosnia and Herzegovina (B&H). The empirical analysis is carried out through the use of the dynamic panel analysis based on the generalized method of moments (GMM) methodology on a dataset of 19 commercial banks operating in B&H in the period from 2006 to 2015. The estimated relationships between excess liquidity and selected variables in models' specifications are as expected. The findings indicate that the size of the bank, non-performing loans and total loans are the key determinants of excess liquidity amongst internal factors. The results also reveal that among the domestic macroeconomic variables CPI is statistically significant indicator of excess liquidity. The commercial banks also rely on foreign markets and the finding arising from this study confirms a significant influence of Eonia on excess liquidity position in B&H. The presented research results and their economic interpretation may have valuable implications on the optimal liquidity management in the commercial banks in B&H and appropriate liquidity supervision. It will also provide beneficial foundation for more thorough liquidity analysis and its possible linkages with other risks within the banking sector.
Keywords: 330